Optimising OSPF Routing to Improve LAN Network Performance - Muhammad Fajrian Noor; Sofyar (Fakultas Teknik Universitas Lambung Mangkurat, 2025)
The performance of a Local Area Network (LAN) greatly depends on the efficiency of the routing protocol applied. This study aims to optimize the configuration of the Open Shortest Path First (OSPF) protocol to improve LAN performance. OSPF is a dynamic routing protocol based on a link-state algorithm that calculates the shortest path using Dijkstra’s algorithm. The research method employed is simulation using Cisco Packet Tracer software. The network topology consists of multiple routers and end-devices, divided into three OSPF areas, each configured with specific IDs, subnets, and IP addresses. The configuration process includes setting IP addresses, assigning OSPF areas, and testing connectivity using ping and traceroute commands. The results demonstrate that OSPF successfully establishes full adjacency between routers, synchronizes the Link-State Advertisement (LSA) database, and ensures optimal routing paths across devices. This implementation proves that OSPF enhances efficiency, convergence speed, and network stability. The study contributes to the development of small to medium-scale LAN networks requiring optimal and reliable data traffic management. It also provides practical insight for network engineers in designing scalable and high-performance routing configurations.